Displacement rate dependence of acrylic adhesive bonded carbon/epoxy composite joints under mode I loading. (8th August 2020) - Mohd Jailani, M. H.; Johar, M.; Gan, K. W.; Wong, K. J.
ABSTRACT: Acrylic adhesives offer design flexibility with its viscoelasticity. However, its use with composite parts has not been studied. In this regard, the aim of this work is to characterise the mode I delamination of acrylic adhesive bonded composite joints subjected to various displacement rates. This study used carbon/epoxy composite as the adherent and 3M adhesive film (VHB 4930F) as the adhesive. Double cantilever beam test was conducted and the mode I fracture toughness GIC was calculated using the simple beam theory. Results show that GIC increases with displacement rate. The maximum GIC is achieved at 500 mm/min, with 155% increment compared to the GIC at 5 mm/min. Furthermore, the cohesive failure is found to be more dominating as the displacement rate increases. Through the quantification of the cohesive area, it is noticed that both GIC and cohesive area correlate well. Both parameters are well fitted using the proposed rate-dependent model.